2011
DOI: 10.1155/2011/352048
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and Aggressive Responses to Frustration: Development of a Questionnaire and Its Validation in a Sample of Male Alcoholics

Abstract: Since clinical and biochemical observations point to much overlap between depression and aggression, both characterised by intolerance to frustration, a questionnaire was developed to test if different patterns of depressive and aggressive reactions elicited by exposure to negative events and deprivation from expected positive ones in human and nonhuman conditions, respectively, would result in specific response patterns in depressive and aggressive persons. The questionnaire was tested for internal consistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…Crawford and Henry [70] found that PA of PANAS has greater explanatory power for depression than NA in non-clinical samples. Consistent with this evidence, many studies have found that frustration elicited by negative feedback is valid in inducing depression [71][72][73][74]. Therefore, in the present study, PA most likely reflects the depression state induced by the frustrating task more sensitively than NA, which may account for the similar NA reports across different groups.…”
Section: Discussionsupporting
confidence: 87%
“…Crawford and Henry [70] found that PA of PANAS has greater explanatory power for depression than NA in non-clinical samples. Consistent with this evidence, many studies have found that frustration elicited by negative feedback is valid in inducing depression [71][72][73][74]. Therefore, in the present study, PA most likely reflects the depression state induced by the frustrating task more sensitively than NA, which may account for the similar NA reports across different groups.…”
Section: Discussionsupporting
confidence: 87%
“…Since in a previous evaluation [28] depression and aggression had been found to be correlated with several of the 16 QDF scales (significant correlations after Bonferroni correction between 10 QDF scales and depression and between 8 QDF scales and aggression), we also computed respective correlations of the QDF scales with impulsivity and anxiety and found 3 significant correlations with impulsivity but none with anxiety (coefficients not shown). Therefore, partial correlations between number of detoxifications and QDF scales were computed by separately controlling for the personality factors of aggression, impulsivity and depression as possible confounders.…”
Section: Resultsmentioning
confidence: 99%
“…(2) The Questionnaire on Daily Frustrations (QDF) by Baars et al [28]. This is composed of 32 items depicting frustrating events, 16 of which represent deprivation from positive reinforcers (non-rewards = pos) and16 refer to the confrontation with negative reinforcements (punishments = neg).…”
Section: Methodsmentioning
confidence: 99%
“…Although human aggression is often seen as a matter of emotional processing, it in fact depends on components of both cognitive and emotional control, ranging from schemas and beliefs driving e.g., threat assessment and behavioral strategies (13, 14) to impulse control and frustration tolerance (15). Given that a nuanced and flexible balance between such processes is needed to generate context-appropriate aggression, it is not surprising that aggression is controlled by a wide network of interconnected cortical and subcortical areas.…”
Section: Introductionmentioning
confidence: 99%